Einfluss von FFF-Prozessparametern auf die elektrische Leitfähigkeit von leitfähigen TPE-Komposite - Salm, Maximilian Karl Franz; Moritzer, Elmar (Technomer 2025 29. Fachtagung)
Keywords: Additive Fertigung; Elektrische Leitfähigkeit; Compounds; TPE; Fused Filament Fabrication

Beitrag zur Reduzierung der Fehlerhäufigkeit bei der Online-Lackierung von SMC-Außenhautbauteilen - Huber, Johannes
Der Verbau von Sheet Moulding Compounds im automobilen Außenhautbereich führt in der industriellen Praxis regelmäßig zu abnehmenden Direktläuferquoten in der Technologie Oberfläche, denn neben bekannten Lackierfehlern ergeben sich auch werkstoff-spezifische Oberflächendefekte, welche einen Bauteilwechsel bedingen. Die hier vorliegende Arbeit soll einen aktiven Beitrag zur Reduzierung von Ausschuss und Nacharbeit entlang der Lackierprozesskette leisten. Zu Beginn werden die erfolgskritischen Oberflächendefekte identifiziert und die zugehörigen Fehlerursachen ermittelt, ehe anschließend die Entwicklung der Fehlstellengrößen in Folge der Temperaturbelastung während der Trocknerdurchfahrten untersucht wird. Ferner soll die Auswirkung einer zusätzlich applizierten Oberflächengrundierung auf die Fehlerhäufigkeit sowie die Oberflächengüte im decklackierten Zustand geprüft werden. Als weitere Möglichkeit zur Problemlösung wird eine in den Prozessablauf integrierte Qualitätskontrolle gesehen, weshalb in dieser Arbeit ebenso die Eignung bekannter zerstörungsfreier Prüfmethoden für die präventive Fehlererkennung überprüft und ein zweistufiges Prüfkonzept erarbeitet wird. Das Aufzeigen möglicher Handlungsalternativen sowie die kostentechnische Gegenüberstellung der verschiedenen Anbauvarianten runden die Arbeit ab.
Keywords: Sheet Moulding Compounds; SMC; Online-Lackierung

Synthesis of lead-free piezoelectric powders by ultrasonic-assisted hydrothermal method and properties of sintered (K0.48Na0.52)NBO3 ceramics - Isobe, G.; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics, Ferroelectrics, and Frequency Control, IEEE Transactions on)
(K,Na)NbO3 ceramics have attracted much attention as lead-free piezoelectric materials with high piezoelectric properties. High-quality (K,Na)NbO3 ceramics can be sintered using KNbO3 and NaNbO3 powders synthesized by a hydrothermal method. In this study, to enhance the quality factor of the ceramics, high-power ultrasonic irradiation was employed during the hydrothermal method, which led to a reduction in the particle size of the resultant powders.
Keywords: Q-factor; ceramics; crystal growth from solution; particle size; piezoelectric materials; potassium compounds; powders; sintering; sodium compounds; ultrasonic effects; (K0.48Na0.52)NbO3; KNbO3 powders; NaNbO3 powders; high-power ultrasonic irradiation; lead-free piezoelectric materials; lead-free piezoelectric powders; particle size reduction; piezoelectric properties; quality factor; sintered (K0.48Na0.52)NbO3 ceramics; sintering; ultrasonic-assisted hydrothermal method; Acoustics; Ceramics; Lead; Piezoelectric materials; Powders; Radiation effects; Transducers

Synthesis of piezoelectric materials by ultrasonic assisted hydrothermal method - Isobe, Gaku; Ageba, Ryo; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (AIP Conference Proceedings)
Hydrothermal method enables to synthesize high quality piezoelectric materials. To shorten the reaction time and to get higher quality materials, we propose an ultrasonic irradiation to the solution during the hydrothermal method. We named it ultrasonic assisted hydrothermal method (UAHTM). We have synthesized lead-free piezoelectric material and PZT thin film and the effect of UAHTM have been confirmed. In this study, we tried to improve UAHTM. First, to generate powerful and stable ultrasonic irradiation at high temperature on UAHTM, we developed a new transducer using LiNbO3 single crystal. Second, to prevent contamination to the materials, A Teflon cover on the tip of transducer was attached.
Keywords: contamination; lead compounds; piezoelectric materials; piezoelectric thin films; piezoelectric transducers; ultrasonic effects

Piezoelectric applications of hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics - Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
A hydrothermal method utilizes a crystallization process in the solution so that the pure and high-quality powders can be realized. Sintering from the hydrothermal KNbO3 and NaNbO3 powders, a high-dense lead-free piezoelectric (K,Na)NbO3 ceramics could be obtained (density: 98.8%). Concerning about the g33 constant, high value as large as commercial PZT ceramics was measured. Therefore, the hydrothermal (K,Na)NbO3 ceramics is usable for the sensors and the energy harvesting devices. To demonstrate the (K,Na)NbO3 ceramics, a hydrophone sensor was fabricated and evaluated.
Keywords: crystallisation; hydrophones; piezoceramics; potassium compounds; powder technology; powders; sensors; sintering; sodium compounds; (K0.48Na0.52)NbO3; KNbO3 powder; NaNbO3 powder; crystallization; energy harvesting devices; g33 constant; hydrophone sensor; hydrothermal lead-free (K0.48Na0.52)NbO3 ceramics; hydrothermal method; piezoelectric applications; sintering; Materials; Transducers